ANALISIS PERUBAHAN GARIS PANTAI DI PANTAI BARAT DAYA PULAU TERNATE, PROVINSI MALUKU UTARA - Abdul Motalib Angkotasan; I Wayan Nurjaya; Nyoman M.N. Natih (Jurnal Teknologi Perikanan dan Kelautan, 2012)
Research is a Shoreline Change Analisis along the South West Coast Ternate Island, North Molucas Province. This study aims to assess the shoreline changes from 2001 to 2011. The research was motivated by the reality on the Southwest Coast Ternate Island, accured abrasion and sedeimentasi to residential areas. There has been no comprehensive study on the extent of shoreline change is happening, and what are the factors that cause these changes. The purpose of this study was to analyze shoreline changes that occur in the Southwest Coast Ternaet island. Shoreline change analysis is done using two approaches that use DHI MIKE LITPACK models and digitized images using Landsat 7 ETM+. The results of image analysis used as a benchmark to validate the model output DHI MIKE LITPACK. Mixed model analysis results collated with the results of image analysis showed patterns of changes in the contour of the same coastline. Based on the analysis model, showed the highest abrasion occurs distasiun C (Sasa Coast) as far as 83.67 m and sedimentation occurred at station B as far as 45.69 m, based on the results of image analysis the highest abrasion occurred at station C of 27.14 m and sedimentation occurred at station E of 24.09 m . The amount of abrasion and sedimentation is affected by wave action that occurs and sand mining activities by the community in Southwest coast of the island of Ternate.